The Effect of Non-immersive Virtual Reality Exergames Versus Band Stretching on Cardiovascular and Cerebral Hemodynamic Response: A Functional Near-Infrared Spectroscopy Study - Zheng, Yuxin; You, Tingting; Du, Rongwei; Zhang, Jiahui; Peng, Tingting; Liang, Junjie; Zhao, Biyi; Ou, Haining; Jiang, Yongchun; Feng, Huiping; Yilifate, Anniwaer; Lin, Qiang (Frontiers in Human Neuroscience, 2022)
Background: Exercise is one of the effective ways to improve cognition. Different forms of exercises have different effects on the improvement of cognitive impairment. In recent years,exergames based on Non-Immersive Virtual Reality(NIVR-Exergames) have gradually been applied to clinical rehabilitation. However, the mechanism of NIVR-Exergames on improving motor cognition has not been clarified. Therefore, the aim of this study is to find whether NIVR-Exergames result in a better neural response mechanism to improve the area of the cerebral cortex related to motor cognition under fNIRS dynamic monitoring in comparison with resistance exercise . Methods: 26 healthy young subjects (18–24 years old) were randomly divided into group A (n = 10) and group B (n = 10) according to a computerized digital table method. Task 1 was an NIVR-Exergame task, and Task 2 was resistance band stretching. Group A first performed Task 1, rested for 30 minutes (i.e., a washout period), and then performed Task 2. Group B had the reverse order. The fNIRS test was synchronized in real time during exercise tasks.The primary outcomes were beta values from the general linear model (GLM) in different regions of interest (ROIs), and the secondary outcomes were heart rate, blood pressure, reaction time of 2-back , and accuracy rate of 2-back . Results: The activation differences of Task 1 and Task 2 in the right premotor cortex (PMC) (P = 0.025) and the left PMC (P = 0.011) were statistically significant. There were statistically significant differences in the activation of the right supplementary motor area (SMA) (P = 0.001) and right PMC (P = 0.001) between baseline and Post-task 1. The differences in systolic pressure (SBP) between the two groups at three time points among women were statistically significant (P1 = 0.009, P2 < 0.001, P3 = 0.044). Conclusions: In this study, we found that NIVR-Exergames combined with motor and challenging cognitive tasks can promote the activation of SMA and PMC in healthy young people compared with resistance exercise alone, providing compelling preliminary evidence of the power for the rehabilitation of motor and cognitive function in patients with central nervous system diseases.